If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6/(3+2)=6/5
We simplify the equation to the form, which is simple to understand
6/(3+2)=6/5
Simplifying:
6/(3+2)=+1.2
Simplifying terms in parentheses
6/(+5)=+1.2
Reorder the terms in parentheses
+(+1.2)=+1.2
Remove unnecessary parentheses
+1.2=+1.2
We move all terms containing to the left and all other terms to the right.
0=+1.2-1.2
We simplify left and right side of the equation.
0=0
0=0
This equation is an identity, so all real numbers are solutions.
| (4y-3)(3y^2+3y-8)= | | x.7-0.5=2.5 | | -16t^2+112t+288=0 | | -16t^2+112t+288=h | | 3k-7.5=16 | | 2(2)+5(5)=15 | | a-15.3=-9 | | 4(5z-1)-5(z+2)=4(z+1) | | 2(4)+5(0)=15 | | r+13.12=1 | | 16t^2+128t+320=0 | | -5(7-10x)= | | 8-3.8k=-4 | | -16t+128t+320=0 | | 5x+5y+5z=300 | | 5y-13=7y-19 | | -32-3.5f=-17 | | -2x+3y=40 | | 1.2y-1.8=7.8 | | 10+3x=2x+9 | | b.3-6=-2 | | .75z-1=.25(z+8) | | 3x^2=7-20x | | 12y-11=y^2 | | 2(x-3)-3(5x-2)=1 | | 16x^2=56x-49 | | 2x+-15x+6-6=10 | | t^2+44+15t=0 | | 3x-4=-x+44 | | 3(x-2)-3=5x-1 | | 6x-9y=-27 | | 7n-28=3(3n-7) |